Peranan Jaksa Agung Muda Bagian Pidana Militer dalam Penanganan Perkara Koneksitas - Putu Nadya Prabandari; I Nyoman Gede Sugiartha; I Made Minggu Widyantara (Jurnal Analogi Hukum, 2022)
Connection criminal in Indonesia is still in orditur condition with prosecutors there has been no technical coordination on handling cases that have the involvement of legal subjects civil with military. The Young Attorney General of the Military Criminal Section was formed handle the connection case. The establishment Section is based on the presidential regulation of the Republic of Indonesia on the organization and work procedures of the Prosecutor's Office which is followed up with regulation of the Prosecutor's Office. Using normative empirical methods with a combining approach between juridical and sociological elements. Reviewing the arrangement of the young attorney general of the military criminal department in handling connection cases and the implementation of handling connection cases at the prosecution stage. Handling of connection crimes can only be tried as a connection case if there is a decision from the Minister of Defense and has been approved by the Minister of Justice. Law enforcement, especially the young attorney general of the military criminal department should establish a connection team in the area to speed up handling connection cases.